Ammonia and Methanol as Energy Carriers Towards 2060 The Long-Term Plan Strategy: A Comparative Perspective of China and Indonesia Cases - Tri Ligayanti; Raldi Hendro Koestoer (Jurnal Ilmu Lingkungan, 2022)
The objective of this paper was to review China’s long-term carbon neutral 2060 policy and to compare with Indonesia’s case in term of energy carriers such as Ammonia and Methanol. Topics regarding China and Indonesia's long-term carbon neutral 2060 policy and strategy are important to be discussed because it will open up issues related to the role of primary energy, chemical-energy nexus and the blue energy economy supported by technology innovation, and political will. The energy-chemical nexus on the background of the Ammonia & Methanol industries are the largest sources of CO2 emissions in China, so it will contribute significantly to emission reductions from the energy transition to carbon neutral energy. From the efforts made by China, it can provide information and considerations to Indonesian policy makers and researchers on their efforts regarding resource management optimization to reconcile the tradeoffs on resources protection and development of socioeconomic as well as to ensure a sustainable system.ABSTRAKTujuan dari makalah ini adalah untuk meninjau kebijakan netral karbon jangka panjang Tiongkok 2060 dan membandingkan dengan kasus Indonesia dalam hal pembawa energi seperti Amoniak dan Metanol. Topik mengenai kebijakan dan strategi jangka panjang karbon netral 2060 Tiongkok dan Indonesia penting untuk dibahas karena akan mengangkat isu terkait peran energi primer, perhubungan energi kimia dan ekonomi energi biru yang didukung oleh inovasi teknologi, dan kemauan politik. Hubungan energi-kimia di latarbelakangi industri Amoniak & Metanol adalah sumber emisi CO2 terbesar di Tiongkok, sehingga akan berkontribusi signifikan terhadap pengurangan emisi dari transisi energi ke energi netral karbon. Dari upaya yang dilakukan oleh Tiongkok, dapat memberikan informasi dan pertimbangan kepada pembuat kebijakan dan peneliti Indonesia tentang upaya mereka mengenai optimalisasi pengelolaan sumber daya untuk mempertemukan timbal balik perlindungan sumber daya dan pengembangan sosial ekonomi serta untuk memastikan sistem yang berkelanjutan.